Services and the smaller economies : challenges and opportunities - Horowitz, Evelyn ([s.n.] [S.l.], 1996)
Analyzes the challenges and opportunities faced by smaller economies with regard to trade in services liberalization in the context of the Free Trade Area of the Americas (FTAA).